Strategi Pengembangan Kreativitas Pada Pedagang Kaki Lima Selama Masa Pandemi (Lembaga Pengembangan Kinerja Dosen, 2022)
One of the micro and small business actors in the informal sector who has felt a significant impact from the Covid-19 pandemic is street vendors (PKL). This research aims to explain the business strategies of street vendors so that they are able to maintain their survival in the businesses that will be carried out (PKL) during the Covid-19 pandemic. This research is included in qualitative research. The subjects of this research were 7 street vendors at SD Karangasem. From the research results, the marketing strategy used by street vendors in the midst of the Covid-19 pandemic is by using social media, including Facebook, Instagram, Whatsapp, Telegram, as well as joining other online businesses such as Shopee, Go-Food, and Grap- food. By using social media, buyers and traders can easily carry out transactions without having to touch each other. So it can be explained that the survival strategy can work as expected by paying attention to consumer purchasing power during the Covid-19 pandemic.